Tokenization efficiency of current foundational large language models for the Ukrainian language - Maksymenko, Daniil; Turuta, Oleksii (Frontiers in Artificial Intelligence, 2025)
Foundational large language models (LLMs) are deployed in multilingual environments across a range of general and narrow task domains. These models generate text token by token, making them slower and more computationally expensive for low-resource languages that are underrepresented in the tokenizer vocabulary. It also makes their usage more costly in such cases, as pricing usually depends on the number of input and output tokens. This study compares multiple tokenizers of pretrained LLMs for the Ukrainian language. It also provides tokenization fertility measurements for current state-of-the-art (SOTA) models, both in terms of general-purpose language and specific domains, as well as results of experiments with a transliteration approach to make tokenization more efficient without information loss. The results provide insights into the current models’ disadvantages and possible problems in terms of Ukrainian language modeling.